‘Getting it into the body’: understanding skill acquisition through Merleau-Ponty and the embodied practice of dance - Purser, Aimie Christianne Elizabeth. (Taylor & Francis, 2017)
This paper responds to calls across the sociological, philosophical and psychological dimensions of Sports Studies to attend to the promise of phenomenology as an approach to understanding the complexities and nuances of embodied athletic experience. The work of the philosopher Maurice Merleau-Ponty is drawn upon to elucidate expertise through a non-dualist framework for understanding skill acquisition and bodily knowledge in sport and movement cultures. In particular, I explore how theoretical concepts about practice might actually play out in practice by bringing the notions of tacit practical knowledge and the sedimentation of habit that Merleau-Ponty emphasises in his theorisation of the corporeal schema into conversation with qualitative data from in-depth interviews with dance practitioners. The paper engages with dancers’ accounts of learning, remembering and performing patterns of movement and, in particular, with the dancers’ notions of having or getting a movement ‘in/into the body’, exploring resonances between these experiences and Merleau-Ponty’s conceptualisation of the habit-body and of incorporating behaviours into the corporeal schema.